#IntersectionalActivism: Tales of origin and intersectional negotiations. Issue 3 (1st November 2019) - Valdivia, Angharad N.
Using a feminist intersectional paradigm, this article explores the invisibilization of intersectional black women and women of colour who initiate movements of hashtag activism. Focusing on #MeToo, #blacklivesmatter, #SayHerName and #OscarsSoWhite, the article explores the process of mediatization that refocuses the social movements on whiteness and/or males. The article finds this to be a continuity between digital and legacy media.